2018
DOI: 10.1007/s00259-018-3996-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased evidence for the prognostic value of FDG uptake on late-treatment PET in non-tumour-affected oesophagus in irradiated patients with oesophageal carcinoma

Abstract: NTO-related tracer uptake during the course of treatment in patients with oesophageal carcinoma was shown to be of high prognostic relevance. Thus, metabolically activity of NTO measured in terms of ∆SUV NTO is a potential candidate for future treatment individualization (i.e. organ preservation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…That may be another reason why the Cox multi-factor regression did not show positive results for ΔTLG in our study. Non-tumour-affected oesophagus (NTO) on restaging PET may be a promising method to deal with the treatment-induced inflammation [34]. Additional PET biomarkers are under investigation for EC right now.…”
Section: Discussionmentioning
confidence: 99%
“…That may be another reason why the Cox multi-factor regression did not show positive results for ΔTLG in our study. Non-tumour-affected oesophagus (NTO) on restaging PET may be a promising method to deal with the treatment-induced inflammation [34]. Additional PET biomarkers are under investigation for EC right now.…”
Section: Discussionmentioning
confidence: 99%
“…152 patients from the Department of Radiation Oncology of the University Hospital Xiamen were included in this study. Imaging and treatment of patients have been previously described 29 , 30 . Briefly, patients received definitive CRT between 2009 and 2013, mostly using intensity modulated radiotherapy (IMRT).…”
Section: Methodsmentioning
confidence: 99%
“…18 Furthermore, recent studies reported a high prognostic value of the FDG uptake within irradiated nontumor affected (o)esophagus (NTO) in a cohort of patients treated with pCRT and dCRT, most likely reflecting radiation-induced inflammation. 21,22 The aim of our study was to confirm that both established interim FDG-PET parameters are prognostic and can identify patients that would be candidates for organ preservation.…”
Section: Introductionmentioning
confidence: 94%
“…Details of the 72 patients from the Department of Radiation Oncology of the University Hospital Xiamen have been previously described. 21,23 Briefly, patients received dCRT between 2009 and 2013, mostly using intensity-modulated radiotherapy (IMRT). After a radiation dose of 50 Gy to the tumor, affected lymph nodes, safety margins, and elective lymph nodes, a consecutive boost of 4-16 Gy was prescribed to tumor/affected lymph nodes (average total dose: 58.9 Gy) with reduced margins.…”
Section: Patients Treatment and Follow-upmentioning
confidence: 99%